FACTORS ASSOCIATED WITH BODY WEIGHT STATUS AMONG CHILDREN WITH AUTISM SPECTRUM DISORDER AGED 2-11 IN KUCHING DIVISION, SARAWAK - Teoh, Wan Jool; Law, Leh Shii; Cheah, Whye Lian (Malaysian Public Health Physicians' Association, 2023)
High prevalence of overweight and obese among children with autism spectrum disorder (ASD) gains attention due to its substantial adverse health impacts. This study aimed to determine the associations between sociodemographic characteristics, parental feeding practices, child eating behaviour, and dietary intake with body weight status of ASD children in Kuching Division, Sarawak. A cross-sectional study was conducted among 124 ASD children (83.9% boys and 16.1% girls) aged 2-11 years, together with their caregivers. The weight and height of ASD children were taken, and body mass index-for-age z-score (BAZ) was computed using AnthroPlus software. Child feeding practices, eating behaviour, and dietary intake were assessed through interviews, with the aid of a questionnaire. Multiple binary logistic regression was used in data analysis. The prevalence of underweight, risk-of-overweight, overweight, and obese ASD children was 3.2% (3.8% boys; 0% girls), 4.8% (2.9% boys; 15.0% girls), 16.9% (17.3% boys; 15.0% girls), and 20.2% (23.1% boys; 5.0 % girls), respectively. The multiple binary logistic regression revealed that the caregivers with high perceived child weight (AOR 31.313, 95% CI=6.127-47.218), high concern towards child weight (AOR 1.774, 95% CI=1.112-2.829), and high sodium intakes (AOR 3.747, 95% CI= 1.515-9.269) were significantly associated with increased risk of overweight or obesity, explaining 37.2% of the variation in body weight status. It is important to prioritise the perspective of caregivers’ feeding practices especially the caregivers with high perceived child weight and concerned child’s weight as well as sodium level of the ASD children while planning for obesity intervention programmes.